HUBUNGAN ANTARA PERSEPSI TERHADAP HARAPAN ORANG TUA DAN MOTIVASI BELAJAR REMAJA MADYA DI JABODETABEK PADA MASA PANDEMI COVID-19 - Nazhira Rana Marhani; Margaretha Purwanti; Aireen Rhammy Kinara Aisyah (MANASA, 2022)
The COVID-19 pandemic requires social distancing, with one of the actions by shifting from faceto-face to online learning. Changes in learning affect students' learning motivation, in this studyis middle adolescence students. Every parent has expectations for their child. Students’perceptions of their parents' expectations are thought to be related to students' learningmotivation. This study aimed to see the relationship between perception of parental expectationsand learning motivation in middle adolescence in Jabodetabek during the COVID-19 pandemic.The researcher adapted the Perception of Parental Expectations Inventory (PPE) measurementtool by Sasikala and Karunanidhi (2011) and developed a learning motivation measurement toolbased on motivational characteristics according to Sardiman (2016). The population in this studywas middle adolescent aged 15 to 18 years who were active students during the COVID-19pandemic in Jabodetabek. The sampling technique is convenience sampling. The research methodused is quantitative with the Pearson correlation test. Participants in this study were 153 people.The results of the correlation test showed that there was a positive and significant relationshipbetween perception of parental expectations and learning motivation in middle adolescence inJabodetabek during the COVID-19 pandemic (r = 0.427, n = 153, p < 0.05, one-tailed). That is,the higher the middle adolescents' perception of their parents' expectations, the higher theirlearning motivation. The lower the middle adolescents’ perceptions of their parents' expectations,the lower their learning motivation. Further research can add learning achievement variable, aswell as differentiate information related to the participants' parents.